Solid base catalytic hydrothermal liquefaction of macroalgae: Effects of process parameter on product yield and characterization. (July 2020) - Biswas, Bijoy; Kumar, Avnish; Fernandes, Alisha C.; Saini, Komal; Negi, Shweta; Muraleedharan, Usha D.; Bhaskar, Thallada
Graphical abstract: Highlights: Different solvents and solid base catalysts was used in macroalgae HTL. Maximum bio-oil (33.0 wt%) was obtained with CaO/ZrO2 (10 wt%) at 280 °C. Solid base catalyst enhanced the compound(s) selectivity. Catalytic HTL bio-oil showed the higher carbon content and HHV. Abstract: The hydrothermal liquefaction (HTL) of Sargassum tenerrimum (ST) macroalgae was carried out for 15 min, over various solid base catalysts (CaO supported on CeO2, Al2 O3, and ZrO2 ) at different reaction temperatures (260–300 °C), different catalyst quantities (5–25 wt%) and using different solvent systems. Maximum bio-oil (BO) yields for the non-catalytic HTL with single solvent water, ethanol, and water-ethanol co-solvent were 3.3 wt%, 23.3 wt%, and 32.0 wt%, respectively, at 280 °C. Ethanol as single solvent elicited highest BO yield of 25.2 wt% with CaO/ZrO2 (10.0 wt%) catalyst. However, the highest BO yield (33.0 wt%) accompanied by higher conversion (70.5%) was obtained with CaO/ZrO2 (10.0 wt%) under water-ethanol co-solvent. The selectively higher percentage of ester functional compounds (87.8%) was found with CaO/ZrO2 catalyst under water-ethanol co-solvent. Also, the bio-oil obtained from catalytic liquefaction showed a higher high heating value (HHV) compared to that from the non-catalytic HTL reaction.